(untitled) (Web of Teachers: Inderscience Research, 2025)
This article focuses on the development of a program aimed at enhancing the self-development competence of future primary school teachers. It discusses the formation of skills and competencies that meet modern teaching requirements. The article highlights innovative approaches in education, the importance of individual and professional development, and the expected outcomes of the proposed program.